2018
DOI: 10.1111/mpp.12761
|View full text |Cite
|
Sign up to set email alerts
|

DCL‐suppressed Nicotiana benthamiana plants: valuable tools in research and biotechnology

Abstract: Summary RNA silencing is a universal mechanism involved in development, epigenetic modifications and responses to biotic and abiotic stresses. The major components of this mechanism are Dicer‐like (DCL), Argonaute (AGO) and RNA‐dependent RNA polymerase (RDR) proteins. Understanding the role of each component is of great scientific and agronomic importance. Plants, including Nicotiana benthamiana , an important plant model, usually possess four DCL proteins, each of which has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 100 publications
2
23
0
5
Order By: Relevance
“…3c), confirming efficient viral replication. This result is in agreement with studies that showed that down regulation of those two DCL in N. benthamiana was associated with increased viral titres for other (+)ss RNA viruses, while individual down regulation of DCL2 or four did not lead to such a result [43].…”
Section: Bsbv Infection On N Benthamiana Down Regulated For Dcl2 Andsupporting
confidence: 93%
See 1 more Smart Citation
“…3c), confirming efficient viral replication. This result is in agreement with studies that showed that down regulation of those two DCL in N. benthamiana was associated with increased viral titres for other (+)ss RNA viruses, while individual down regulation of DCL2 or four did not lead to such a result [43].…”
Section: Bsbv Infection On N Benthamiana Down Regulated For Dcl2 Andsupporting
confidence: 93%
“…Seeds of this cultivar were first uncoated using 10 % (v/v) EtOH. Transgenic N. benthamiana lines down regulated for DCL (DCL1.13i, DCL2.11i, DCL3.10i, DCL4.9i, DCL2/4.5i) have been described before [42, 43].…”
Section: Methodsmentioning
confidence: 99%
“…These results suggested a main involvement of DCL4 and DCL2 in anti-PLPV silencing as reported in other plant–virus combinations [11, 38, 39]. In order to confirm, or refute, this possibility, we used a genetic approach by taking advantage of the previous creation of a collection of N. benthamiana transgenic lines in which the different DCL genes were downregulated, either individually or in combinations, through an RNAi approach [33, 34, 40]. This collection included either single DCL RNAi lines (henceforth DCL1i, DCL2i, DCL3i or DCL4i) or double (DCL2/4i) and triple (DCL2/3/4i) DCL RNAi combinations.…”
Section: Resultsmentioning
confidence: 77%
“…[44] The benefit of this method is the detection of different strains of the same virus with the use of only one probe. [48,49] In 1977, a modification of this technique, named northern blot, was created, specialized in the detection of RNA molecules, soon used also for viral and viroidal detection.…”
Section: Southern and Northern Blotsmentioning
confidence: 99%